HEADACHE, TEMPOROMANDIBULAR DISORDERS AND SELF-MEDICATION: FINDINGS FROM A LARGE SAMPLE QUESTIONNAIRE STUDY INVOLVING 1019 PARTICIPANTS - Manuela Lalu; Marius Sorin Pop; Olivia Andreea Marcu; Petru Mihancea (Romanian Society of Oral Rehabilitation, 2023)
The aim of this study was to assess the prevalence of temporomandibular disorders in patients suffering from headaches and the association of several types of headache in the same patient. Material and methods: We carried out a research based on the survey technique, using an online-managed questionnaire as tool. The questionnaire we used included elements as suggested by the International Headache Society (IHS) and was intended to identify both the headache form and the TMD specific symptomatology. The total number of respondents was 1019. Results: We were able to identify a close relation between headache and TMD. The data analysis shows an increased prevalence of headaches in women. The questionnaire revealed that a higher percentage of the respondents (33,9%) suffer from one type of headache, and is closely followed by a percentage of 27,7% suffering from two associated types and we regrettably noticed an increased frequency of persons preferring to self-medicate. Conclusions: We were, thus, able to demonstrate a close relation between TMD and headache, but we are rather concerned about the fact that a considerably large number of respondents prefer the self-medication option. This is a very alarming issue for the medical system in Romania.